Digital competencies of teachers in elementary education: challenges and possibilities in the use of digital technologies - Souza Paula , Rita de Cássia de; Furnival, Ariadne Chloe Mary (Universidade Federal de São Carlos, 2026)
Objective: This article aims to identify and promote reflections on the challenges faced by elementary school teachers in the use of Digital Information and Communication Technologies (DICT) in their teaching practices. Theoretical Framework: The research is based on the investigation of teachers' digital skills, based on the European DigCompEdu framework, in line with Brazilian public policy: the Connected Education Innovation Program. Method: To this end, an exploratory-descriptive study was conducted using a mixed approach with qualitative and quantitative aspects. Snowball sampling was used to locate the research subjects, resulting in 47 teachers from the states of Minas Gerais and São Paulo who work in schools covered by the Program. Results and Discussion: The data revealed that, although there have been advances in technological integration policies, challenges and difficulties still persist, such as inadequate infrastructure, unstable connections, lack of technical support, and teacher resistance to the use of TDICs. Gaps were also identified in relation to continuing education and insecurity regarding the handling of digital resources. Research Implications: Therefore, in addition to investing in infrastructure, it is essential to expand continuing education policies planned in a way that respects the reality of teachers, encouraging innovative and critical pedagogical practices aligned with contemporary demands. Originality/Value: The more effective integration of TDICs into basic education therefore requires integrated strategies that consider the structural, technical, human, and training aspects of teaching practice.
Keywords: teaching competence; teachers; elementary school; technology and education; Sustainable Development Goals (SDGs); 4. Educação de Qualidade